Sovereignty and Responsibility in a Multilevel System: Subsidiarity as the Guiding Principle? - Michael Hüther; Markus Vogel (Wirtschaftsdienst)
Abstract In the German political debate, the principle of subsidiarity plays an important role in the acceptance of the European multilevel system. In such a system, there is a collision of historically diverging, systematically inconsistent and qualitatively different needs. This combination demands an “active subsidiarity” and a “subsidiarity routine” in order to dynamically shape the heterogeneous EU. This way, we may find a balance between the needs of the citizens (acceptancy), the EU institutions (efficiency) as well as of the different levels of decision making and acting (reason for being). Above all, subsidiarity must start at home, it can be strengthened in the EU if it does not erode in the member states. This challenge has been regularly neglected til now.